THE EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING (PBL) STRATEGY IN LEARNING ENGLISH IN 10TH GRADE STUDENTS IN MA MAMBAUL ULUM MEGALUH JOMBANG - Yuyun Bahtiar (Universitas KH. A. Wahab Hasbullah, 2019)
This study uses classroom action research using PBL Method. The sample is Madrasah Aliyah Mambaul Ulum Megaluh Jombang. Consisting of 30 Students, 14 male students and 16 female students. The study was conducted in two cycles; one cycle was carried out twice. Techniques used for data collection include observation sheets and test sheets during the action and documentation of learning activities. The results of this study indicate the initial ability test of students who completed 20%. Furthermore, acted on cycle I with PBL method that student learning outcomes in English Subject Congratulations matter can be known as many as 56.67% declared complete Then through post-test cycle II proved that student learning outcomes in English subject matter Congratulations as much as 80% were declared complete. Based on the comparison of these numbers, it can be stated that the acquisition of the results of the post-test cycle II experienced completeness in student learning outcomes. This proves that it is not necessary to take corrective action through the implementation of the next cycle.